Spinal Cord Pathology in Alpha-Synuclein Transgenic Mice - Sonja Mendritzki; Saskia Schmidt; Teresa Sczepan; Xin-Ran Zhu; Daniel Segelcke; Hermann Lübbert (Parkinson's Disease)
Accumulation of α-synuclein is observed in neurodegenerative diseases like Parkinson's disease and Multiple System Atrophy. In previous studies with transgenic C57BL/6 mice overexpressing α-synuclein carrying the mutations A53T and A30P found in Parkinson's disease or with a parkin-null background, we reported severe mitochondrial impairments in neurons and to a larger extent in glial cells of the mesencephalon. Neuron death was not observed in the brain. Here we show that the mice show severe motor impairments in behavioral tests. In addition, these mice exhibit astrocytic cell death in the spinal cord, accompanied by extensive gliosis and microglial activation. This is shown by cell death staining and immunohistochemistry. Ultrastructural analyses revealed severe mitochondrial impairments not only in astrocytes, but also in oligodendrocytes and, to a small extent, in neurons. Thus, the transgenic mice show a profound pathology in glial cells of the spinal cord.